2001
DOI: 10.1515/jpem.2001.14.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Impaired Glucose Tolerance in Patients with Cystic Fibrosis and Predisposition Factors

Abstract: A high percentage of patients with CF also present with IGT. This increases with age and is more common among patients homozygous for the deltaF508 mutation and is not related to clinical status. Alterations in the kinetics of insulin secretion play an important role in the appearance of IGT and CF. We suggest that the OGTT is a more sensitive method than IVGTT for identifying early alterations in CF-related diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
3
10
1
3
Order By: Relevance
“…Similar results were obtained with the intravenous glucose tolerance test (IVGTT) technique (23,39,(42)(43)(44). Both methods are unsuitable for large-scale and repeated assessment.…”
Section: Introductionsupporting
confidence: 64%
“…Similar results were obtained with the intravenous glucose tolerance test (IVGTT) technique (23,39,(42)(43)(44). Both methods are unsuitable for large-scale and repeated assessment.…”
Section: Introductionsupporting
confidence: 64%
“…Glucose intolerance was strongly associated with pancreatic insufficiency. 31,32 Milla et al 13 followed 152 patients with CF over 4 years and found a higher prevalence of impaired glucose tolerance than in our study. At baseline, 45% of their patients * Multivariate analysis of variance with sex and glucose-tolerance group as fixed factors.…”
Section: Discussionsupporting
confidence: 48%
“…This document states that nutritional and metabolic consequences of IGT in CF patients are still unknown and thus no specific guidelines for management are given, except for a close follow up to detect the onset of CFRD. However, recent studies pointed towards mild glucose metabolism alterations as a cause of clinical deterioration in patients with CF (23,24).…”
Section: Introductionmentioning
confidence: 99%